Effects of Bio-Psycho-Socio-Spiritual Factors on Biomarkers of Cardiovascular Inflammation in Elderly Indonesian Muslim - Yusuf Alam Romadhona; Bambang Purwantob; Rochmad Romdonic; Surotod (Asian Journal of Medical Research, 2020)
Background: The evaluation of bio-psycho-socio-spiritual factors on cardiovascular inflammatory biomarkers has not been widely studied in Indonesia. Accumulated evidence that biological, psychosocial and spiritual factors were related to the incidence, severity and cure of cardiovascular disease through psycho-neuro-immunological pathways. Objective: This study was conducted to analyze the effect of bio-psycho-socio-spiritual factors on cardiovascular risk and inflammatory biomarkers.Subjects and Methods:A total of 121 subjects voluntarily participated in the study, were recruited using the cluster random sampling method from Posyandu (Indonesian health service). Each subject was examined for ELISA blood examination of the high sensitive C-reactive protein, transforming growth factor-b, intracellular adhesion molecule-1 and interferon-g. The subjects filled out the depression anxiety stress scale-42 questionnaire for stress, anxiety and depression; WHOQOL BREF for quality of life and the solemnity questionnaires for the solemnity in Islamic prayer measurement. The assessment for cardiovascular risk using the Jakarta score method.Results:The biophysical factors which influence inflammatory biomarker include blood pressure on ICAM-1 and hs-CRP, body mass index on TGF-b, and fasting blood glucose on hs-CRP. The influence of psychosocial factors include educational degree on ICAM-1 and hs-CRP, marital status on cardiovascular risk and depression on blood pressure. The solemnity in Islamic prayer is a spiritual coping that have effect on improving the quality of life.Conclusion: The biophysical factors having influence on inflammatory biomarker are blood pressure, body mass index and fasting blood glucose. The contribution from psycho-socio-spiritual factors include educational degree, marital status and depression.